MENINGKATKAN KINERJA DAN WELL-BEING PENGRAJIN BATIK GENTONGAN MADURA MELALUI KOMPETENSI SUMBER DAYA MANUSIA (SDM) DAN SOCIAL CAPITAL (STUDI PADA PENGRAJIN DI KABUPATEN BANGKALAN, MADURA) - Asman; Hasanah, Uswatun (Universitas Muhammadiyah Pontianak, 2026)
Madura Gentongan batik artisans face low performance and welfare due to limited HR competencies and suboptimal social capital. This study examines how HR competencies and social capital affect performance and well-being, with performance as a mediator. Using PLS-SEM on survey data from 170 artisans in Bangkalan, results show HR competencies significantly enhance performance and well-being, directly and indirectly. Social capital improves performance but not well-being, due to the dominance of bonding ties that generate social pressure. The study highlights HR competencies as key to improving artisan welfare, while social capital’s direct impact remains limited.